Human–climate–environment interactions in Espiritu Santo, Vanuatu during the past millennium - Camperio, Giorgia; Ladd, S. Nemiah; Prebble, Matiu; De Jonge, Cindy; Schneider, Tobias; Argiriadis, Elena; Lloren, Ronald; Nelson, Daniel B.; Delahaie, Amicie A.; Krentscher, Christiane; Dubois, Nathalie (Frontiers in Earth Science, 2025)
Over the past millennium, the tropical Pacific Islands of Remote Oceania have experienced significant transformations caused by different waves of human settlement and climatic variability. However, many sites remain to be explored for their archeological potential, and the complex climatic setting of the tropical Pacific further complicates our understanding of past environmental and societal changes. In this study, we applied a multi-proxy approach to sediment cores extracted from ponds on the west coast of Espiritu Santo, Vanuatu to investigate past human-climate-environment dynamics. Through the analysis of human-associated proxies including fecal markers, palmitone (a specific lipid biomarker for taro), crop pollen and sedimentary charcoal, we inferred changes in human presence and activities. We reconstructed past hydroclimate from leaf wax hydrogen isotopes (δ2HLW) and past temperatures from branched glycerol dialkyl glycerol tetraethers (brGDGTs). Changes in pollen reveal major shifts in local and regional vegetation. In our record, the period from 1000 to 1300 CE was characterized by warm/wet conditions concomitant with demographic expansion inland. Around 1400 CE, pollen, leaf wax distributions, and δ2HLW data indicated a drier period. The coincident decrease in palmitone, despite high charcoal and fecal marker concentrations, suggested that drier conditions might have rapidly restricted taro cultivation, but not the overall population, which declined more than a century later. We hypothesize that the establishment of one of the earliest European settlements in Oceania in 1606 CE further disrupted local demographics with the introduction of epidemic diseases. This study contributes to our understanding of the intricate relationship between human activities, climatic fluctuations, and landscape modifications in Remote Oceania over the past millennium.